WAKTU TUMBUH MATA TUNAS DAUN Mangifera indica L. PADA BERBAGAI TINGKATAN - Dede Fajar; Tri Cahyanto; Afriansyah Fadillah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
Fenology including one of scientific that study about development phases such as flowering character or development of leaf. One of leaf’s development M.indica leaf has a very high diversity such as shape size even the color is often different according to its development as well as the buds that appear in the plan. The observation of buds’s growth period in the M.indica plan has ever done before, but the levels and the time is still not clear. This research aimed to know the buds’s time grows on various levels of M. indica so obtained the good appearance time and the level of M.indica species for further research material. The collecting data uses exploration method by exploring the area of sub-district Cibiru, district Bandung, West Java and an act of determine a level. The act of determine of the length and the diameter of each stand which is found at the three regions. The result of observation shows 7 of the 12 specimen that has been observed experiencing the growth of leaf buds. The average growth time of the buds in the specimen that experienced a growth is 13 days which dominate with pole, as for the existence of the variation of shape and bud color appearance enable to the existence of growth to the next phase from that buds.